2020
DOI: 10.3390/w12010162
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Annual Maximum and Minimum Flow Trends in a Data-Scarce Basin. Case Study of the Allipén River Watershed, Chile

Abstract: Data on historical extreme events provides information not only for water resources planning and management but also for the design of disaster-prevention measures. However, most basins around the globe lack long-term hydro-meteorological information to derive the trend of hydrological extremes. This study aims to investigate a method to estimate maximum and minimum flow trends in basins with limited streamflow records. To carry out this study, data from the Allipén River watershed (Chile), the Hydrologiska By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The Allipén River rises in the Andes Mountains, in the southern part of Chile, specifically in the La Araucanía region (Medina and Muñoz, 2020;Vargas et al, 2010), afterwards receives the waters of Trufultruful River and Zahuelhue River, it has a 108 km length and a 2,325 km 2 basin area (Figure 1). The river drains to the northern part of the Toltén basin and ends its route 15 km east of Pitrufquén, leading to the Toltén river (38º51'S and 71º45'W) (DGA, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The Allipén River rises in the Andes Mountains, in the southern part of Chile, specifically in the La Araucanía region (Medina and Muñoz, 2020;Vargas et al, 2010), afterwards receives the waters of Trufultruful River and Zahuelhue River, it has a 108 km length and a 2,325 km 2 basin area (Figure 1). The river drains to the northern part of the Toltén basin and ends its route 15 km east of Pitrufquén, leading to the Toltén river (38º51'S and 71º45'W) (DGA, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…This insignificant trend in most seasons before and after the changing point indicates a decrease in the statistical significance of hydroclimatic variable trends as the data years are limited or below ten years, which the World Meteorological Organization (WMO) recommends for data-scarce regions [95]. Correspondingly, a study in Chile estimating annual maximum and minimum flow trends [96] revealed higher uncertainty and less significance of trend results for the limited data length than longer years.…”
Section: Hydroclimatic Variables Trend Analysismentioning
confidence: 99%